Synthesis of 7-Phenyl-5-Keto-Heptoa-6-7-ene and 6-Phenyl-Hexa-4-Keto-5-6-ene the Intermediates in the Syntheses of Norleucine and Norvaline - Limaye, P.A.; Nimse, M.S.; Ghate, S.M. (Asian Journal of Chemistry, 2010)
Syntheses of compounds which will serve as intermediates in the syntheses of norvaline and norleucine have been reported herewith. Kolbe process of electro organic synthesis has been used for the same.